A core@dual-shell nanorod array with a cascading band configuration for enhanced photocatalytic properties and anti-photocorrosion. Issue 7 (30th January 2020) - You, Daotong; Xu, Chunxiang; Wang, Xiangxiang; Wang, Jing; Su, Wenyue; Wang, Ru; Chen, Tianlang; Wang, Ru; Shi, Zengliang
Abstract : ZnO–CdS–NiOx core@dual-shell nanorod arrays with cascade electron and hole transfer between them for high-performance photocatalytic H2 production. Abstract : Core–shell nanorod geometry is an ideal structure to combine multiple materials on a nanoscale system, consequently overcoming the drawbacks of single materials and generating new synergistic properties. Here, we report an effective strategy combining vapor-phase deposition and a two-step sputtering method to achieve core@dual-shell nanorod arrays consisting of ZnO nanorod inner core, visible-light-responsive CdS middle shell and p-type NiOx outer shell with a cascading band configuration between them. The optimized ZnO–CdS–NiOx, as a photocatalyst, exhibits superior photocatalytic activity under simulated sunlight irradiation, with excellent H2 evolution rate (84 834 μmol h −1 g −1 ) and high apparent quantum efficiency (33.89% at 380 nm), which is 420.8, 42.7, and 4.2 times higher than that of the bare ZnO, bare CdS and ZnO–CdS core–shell nanorods, respectively. Furthermore, it also shows long-term stability, remaining at 97.4% of the initial value after 36 h. This attractive photocatalytic behavior and photostability is ascribed to the unique core@dual-shell structure and rational energy band engineering, which improve light absorption as well as enhance charge carrier separation via the intimate contact interface and the band structure of ZnO synergistically cascading with CdS and NiOx. It is expected to provide a scalable route to constructing well-defined core–shell nanostructures for high-performance photocatalytic applications.